2019
DOI: 10.1186/s13638-019-1433-1
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement learning-based dynamic band and channel selection in cognitive radio ad-hoc networks

Abstract: In cognitive radio (CR) ad-hoc network, the characteristics of the frequency resources that vary with the time and geographical location need to be considered in order to efficiently use them. Environmental statistics, such as an available transmission opportunity and data rate for each channel, and the system requirements, specifically the desired data rate, can also change with the time and location. In multi-band operation, the primary time activity characteristics and the usable frequency bandwidth are dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…This dataset consists of 24 different types of attacks that are divided into four groups: DDOS, Probe, U2R, and R2L. According to some studies [30][31][32], the filtered 10% KDDCUP99 data described as shown in Table 5 is used when dealing with lots of network intrusion detection issues. In the experiments, the dataset is partitioned into two parts: 50% of data is utilized as training data and the remaining 50% data is considered as testing data.…”
Section: Kddcup99 Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This dataset consists of 24 different types of attacks that are divided into four groups: DDOS, Probe, U2R, and R2L. According to some studies [30][31][32], the filtered 10% KDDCUP99 data described as shown in Table 5 is used when dealing with lots of network intrusion detection issues. In the experiments, the dataset is partitioned into two parts: 50% of data is utilized as training data and the remaining 50% data is considered as testing data.…”
Section: Kddcup99 Datamentioning
confidence: 99%
“…In the experiments, the dataset is partitioned into two parts: 50% of data is utilized as training data and the remaining 50% data is considered as testing data. Moreover, in order to compare with other models, we also used the existing performance index [27][28][29][30][31][32]:…”
Section: Kddcup99 Datamentioning
confidence: 99%
“…It estimates channel state for the next time instant and uses this estimation to rank and select the operating channel in clustering. In [20], the optimal band and channel selection mechanism for cluster-based CRN is proposed. Based on each MN's reporting in terms of spectrum sensing and traffic demand, CH determines cluster's operating band and channel using Q-learning.…”
Section: Related Workmentioning
confidence: 99%
“…In [12], the authors proposed the use of a Q-learning based dynamic optimal band and channel selection scheme, which took into account the surrounding wireless environments and system demands in order to maximize the available transmission time and capacity at the given time and geographic area. The simulation results showed that their solution dynamically chose a band and channel suitable for the required data rate and operated properly according to the desired system performance.…”
Section: Related Workmentioning
confidence: 99%